Fractional order PID Design using the Taguchi method - Somayeh Nouruzi Ghazbi; Alireza Akbarzadeh (IAES International Journal of Robotics and Automation (IJRA), 2015)
This paper presents a gain-tuning scheme for Fractional order PID control systems using the Taguchi method. A prismatic series elastic actuator is selected as an experimental set-up. An optimal controller gains has been obtained through a series of experiments suggested by the Taguchi method. Four stages of tuning are performed in order to accurately tune the controller gains. It is shown that when performance of the proposed controller is compared with two additional controllers: a traditional FOPID tuned with Ziegler-Nichols (Z-N) method and a PID tunned with genetic algorithm, a 94% and 84% improvements in position error is observed, respectively.